1D NiO–3D Fe2O3 mixed dimensional heterostructure for fast response flexible broadband photodetector. (4th June 2022) - Reddy B, Kumaar Swamy; Veeralingam, Sushmitha; Borse, Pramod H; Badhulika, Sushmee
Abstract: Conventional heterojunction photodetectors rely on planar junction architecture which suffer from low interfacial contact area, inferior light absorption characteristics and complex fabrication schemes. Heterojunctions based on mixed dimensional nanostructures such as 0D-1D, 1D-2D, 1D-3D etc have recently garnered exceptional research interest owing to their atomically sharp interfaces, tunable junction properties such as enhanced light absorption cross-section. In this work, a flexible broadband UV–vis photodetector employing mixed dimensional heterostructure of 1D NiO nanofibers and 3D Fe2 O3 nanoparticles is fabricated. NiO nanofibers were synthesized via economical and scalable electro-spinning technique and made composite with Fe2 O3 nanoclusters for hetero-structure fabrication. The optical absorption spectra of NiO nanofibers and Fe2 O3 nanoparticles exhibit peak absorption in UV and visible spectra, respectively. The as-fabricated photodetector displays quick response times of 0.09 s and 0.18 s and responsivities of 5.7 mA W −1 (0.03 mW cm −2 ) and 5.2 mA W −1 (0.01 mW cm −2 ) for UV and visible spectra, respectively. The fabricated NiO–Fe2 O3 device also exhibits excellent detectivity in the order of 10 12 jones. The superior performance of the device is ascribed to the type-II heterojunction between NiO–Fe2 O3 nanostructures, which results in the localized built-in potential at their interface, that aids in the effective carrier separation and transportation. Further, the flexible photodetector displays excellent robustness when bent over ∼1000 cycles thereby proving its potential towards developing reliable, diverse functional opto-electronic devices.